La idea fichteana de la propiedad. Sus limitaciones en el plano de la intersubjetividad (Revista Eletrônica Estudos Hegelianos, 2016)
In this paper I aim to show that the Fichtean idea of the right to property, originally conceived to protect the relationship of mutual recognition between citizens, actually ends up blocking this very relationship, because it assumes the conception of the other as an enemy and not an alter ego of the I. Finally I compare the Fichtean theory of the right to property with the one elaborated by Hegel, who managed to preserve the relationship of mutual recognition, making each other´s subjectivity possible.